PEMBENTUKAN KELOMPOK GENERASI REMAJA CEGAH STUNTING (GEMAR CETING) DI SMA NEGERI 2 KOTA LAMA KECAMATAN RENGAT BARAT - Julita, Sety; Aryani, Yeni (PITIMAS: Journal of Community Engagement in Health, 2025)
Stunting in children can occur due to the lack of special attention in the first 1000 days after birth, because this period determines the level of physical growth, intelligence, and productivity of a child in the future (Ni'mah & Lailatul, 2015). Adolescent behavior The low public knowledge of the factors that cause stunting and its prevention has resulted in people becoming very vulnerable to having a stunted generation. From the academic side, the community service team views that health training, especially regarding stunting in adolescent groups, needs to be carried out as an early anticipation and optimization of the role of the community in this program. Adolescents are members of society who are able to become agents of change. Activities to Improve Adolescent Behavior Through the Formation of the Youth Movement to Prevent Stunting (GEMAR CETING) group with the game Se Tatak at SMA Negeri 2 Kota Lama, West Rengan District, which is the working area of the Pekan Heran Health Center, is expected to be able to change adolescent behavior and increase adolescent knowledge and share knowledge with peers.